IMPROVING ENGLISH SPEAKING SKILLS IN HOSPITALITY SECTOR FOR SECOND GRADE STUDENTS OF AL MA'ARUF NU SINAH HIGH SCHOOL - Evi Safitri Yulandari (JURNAL ILMIAH GLOBAL EDUCATION, 2021)
The development of tourist attractions in the central Lombok area must be accompanied by an increase in human resources, especially in the field of English, because of the increasing regional progress which is marked by developments in terms of better arrangement of tourist attractions, especially in the Lombok area. Central, so it has attracted local and foreign tourists to be able to visit these places, such as: Selong Belanak Beach, Kuta beach, An Beach, Sade Village, etc. The development of these human resources can be in the form of providing English courses or at least teaching English that focuses on the field of English for the second grade high school level. In addition to creating skills for students, students can also become responsible workers; this can also develop village potential, can also foster students to actively support government programs in the tourism sector. This research was carried out with the aim of improving English speaking skills in the hospitality sector for Al Ma'aruf Nu Sinah High School students in Pengembur Village, Central Lombok, and this study used a qualitative descriptive method to find out how much the improvement in English skills of second grade students of Al Ma'aruf Nu Sinah High School after this research was conducted. The results of research activities carried out by researchers in 3 months showed an increase in the ability to speak English in a simple form in the hospitality sector for students at Al Ma'aruf Nu sinah high school in Pengembur Village, Central Lombok.